The Effect of Ease of Transaction and User Interface (UI) Design on User Interest in Using the Bank Jago Application with User Satisfaction as an Intermediary Variable - Raniyah Kamilah; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Journal of Strategic Marketing and Innovation, 2025)
This study seeks to examine the influence of transaction convenience and user interface design on users’ intention to use the Bank Jago application, with user satisfaction serving as a mediating variable. The study employs a quantitative methodology using the SmartPLS application and a partial Least Squares-based Structural Equation Modeling (SEM-PLS) technique. Data were gathered using questionnaires administered to Bank Jago users aged 18 years and above who had conducted transactions. The findings demonstrate that user interest in the application is positively impacted by transaction ease and interface design. Furthermore, it has been demonstrated that user happiness functions as a mediating factor in the relationship between transaction wase, interface design, and interest in utilizing the Bank Jago application. These findings emphasize the importance of ease and quality of application design in increasing satisfaction and interest in using digital banking service.